Implementasi Sistem Informasi Akuntansi Dalam Pengelolaan Keuangan Pada Pelaku Usaha Mikro Kecil Menengah (UMKM) : (Studi Kasus pada pelaku Usaha Mikro Kecil dan Menengah di Kecamatan Surade Kabupaten Sukabumi) - Rizwan Nurdiansyah; Sulaeman Sulaeman; Idang Nurodin (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This research aims to analyze the implementation of accounting information systems in financial management for Micro, Small and Medium Enterprises (MSMEs) in Surade District, Sukabumi Regency. In this digital era, the use of accounting information systems is very important to increase the efficiency and effectiveness of financial management. MSMEs often face challenges in financial management caused by limited resources and lack of accounting knowledge. The method used is qualitative with a descriptive approach. The research results show that MSEs in Surade sub-district have not partially implemented financial information systems in financial management.